2012
DOI: 10.1038/bmt.2012.209
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children who experience disease relapse following allogeneic hematopoietic SCT for hematologic malignancies

Abstract: Relapse after allogeneic hematopoietic SCT (HSCT) carries a poor prognosis and is a common cause of death. Outcomes of children who relapse post HSCT are not well known. In this retrospective multicenter study we included 532 patients who underwent allogeneic HSCT and examined the outcomes of 160 patients (30%) who relapsed. Treatment options after relapse included (i) palliative therapy with non-curative intent (n ¼ 43), (ii) salvage chemotherapy (without a second HSCT, n ¼ 55) or (iii) salvage chemotherapy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 10 publications
6
20
0
Order By: Relevance
“…Unlike what has been observed in adult patients, pediatric patients who received a second HSCT had a significantly improved survival compared to those who were treated with salvage therapy without HSCT (35% vs 2%). 8 It is also clear from our data that there is no consistent approach regarding the preparative regimen, intensity or timing of the second HSCT. A report from the CIBMTR on the outcome following second allogeneic HSCT in patients with acute and chronic leukemia found that patients younger than 20 years and those who relapse 46 months from the first HSCT have improved survival.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Unlike what has been observed in adult patients, pediatric patients who received a second HSCT had a significantly improved survival compared to those who were treated with salvage therapy without HSCT (35% vs 2%). 8 It is also clear from our data that there is no consistent approach regarding the preparative regimen, intensity or timing of the second HSCT. A report from the CIBMTR on the outcome following second allogeneic HSCT in patients with acute and chronic leukemia found that patients younger than 20 years and those who relapse 46 months from the first HSCT have improved survival.…”
mentioning
confidence: 76%
“…[8][9][10][11][12][13] In a study by the Seattle group the authors reported on the outcome of 307 adult patients who relapsed following HSCT. The 2-year survival was 3-19% depending on the time from transplant to relapse, with those experiencing relapse 4200 days having the best outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within relapsed patients, high risk groups are identifiable by timing and site of relapse and have a long term event free survival of 30% or less even with allogeneic stem cell transplantation (allo-sct) 3,5,6 . The outcomes of those relapsing following allo-sct are dismal, with long term survival of only 10-20% in those undergoing second transplantation procedures [7][8][9] , which was also associated with significant adverse toxicity. For these groups, novel therapies were urgently needed, and access to CAR T cell therapy has been a "game-changer" in terms of outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…(3, 4, 6) However, with frequent post-transplant surveillance and more sensitive measures of detection, disease recurrence could, in theory, be detected both earlier and at a state of lower disease burden that may be more amenable to treatment, potentially leading to improved outcomes. (1012) Certainly, preemptive immunotherapy in the setting of mixed chimerism has shown promise in relapse prevention.…”
Section: Introductionmentioning
confidence: 99%